Potential Utilization of Municipal Solid Waste in Landfill Mining TPST Bantargebang Bekasi to Become Refuse Derived Fuel (RDF) Feed Stock - Teti Resmianty; Anas Miftah Fauzi; Edy Hartulistiyoso; Setyo Pertiwi (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2022)
Bantargebang Integrated Waste Management Site (TPST) is a final waste processing site that accommodates waste from the DKI Jakarta Province. Most of the waste that enters the Bantargebang TPST is piled up at the dumping point in each zone, so this can lead to a new problem, namely the filling of all existing stockpile zones. One of the technologies that can be used to solve the problem of full landfill zones. One technology to overcome this problem is landfill mining. The results of the study related to landfill mining at the Bantargebang TPST were carried out to determine the potential for utilizing landfill mining waste to become RDF feed stock. Based on the study of the composition of landfill mining results carried out, the waste to be used as raw material for RDF is waste with a diameter > 50 mm and which has a high calorific value.